Urea-formaldehyde resin base plate as well as preparation process and application thereof

By using a composite of paraformaldehyde and aqueous formaldehyde solution to react with urea, the urea-formaldehyde resin pads are solved, and the high hardness, low warpage and environmental protection are achieved. It is suitable for micro-hole drilling processing of highly integrated printed circuit boards.

CN119749039AActive Publication Date: 2025-04-04SHENZHEN NEWCCESS IND CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411959123.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing phenolic resin pads have shortcomings in the high cost, environmental pollution and warping problems, and it is difficult to meet the needs of highly integrated, high-density and high-reliability printed circuit boards.

Method used

A composite of paraformaldehyde and aqueous formaldehyde solution reacts with urea to form urea-formaldehyde resin, and a semi-cured sheet is formed by baking, and superimposing it on a wood fiber board for pressing, to prepare a urea-formaldehyde resin pad with high hardness and low warpage.

Benefits of technology

It significantly reduces the cost of the pad, improves environmental protection, enhances the hardness and warpage resistance of the pad, extends the service life of the drilling needle, and is suitable for micro-hole drilling processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119749039A_ABST
    Figure CN119749039A_ABST
Patent Text Reader

Abstract

The invention discloses a urea-formaldehyde resin base plate and a preparation process and application thereof.The preparation process of the urea-formaldehyde resin base plate comprises the following steps that urea-formaldehyde resin is adopted for impregnating surface paper, the impregnated surface paper is made into prepregs through baking, then the prepregs are overlaid on the upper side and the lower side of a wood fiber plate respectively, and finally pressing forming is conducted through a pressing machine, so that the urea-formaldehyde resin base plate is obtained. The base plate is obtained; wherein the urea-formaldehyde resin is obtained by reacting a compound of paraformaldehyde and a formaldehyde solution with the solubility of 35-40% with urea. The urea-formaldehyde resin base plate prepared through the preparation technology has the advantages of being high in hardness, low in warping and excellent in punching performance, the preparation technology reduces the manufacturing cost of the drilling base plate, and the drilling base plate is environmentally friendly, can meet the market requirement and is widely applied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of printed circuit board drilling, and in particular to a urea-formaldehyde resin pad and a preparation process and application thereof. Background Art

[0002] As printed circuit boards (PCBs) develop towards high integration, high density and high reliability, micro-hole drilling (aperture of 0.2mm and below) has become popular. Micro-hole drilling generally uses phenolic pads, which require the pad thickness center value to be 1.50mm, good surface flatness (tolerance ±0.10mm), good Shore hardness (80 and above) and pencil hardness (5H and above), and small warping (<0.5%). At present, this type of pad is made by stacking multiple phenolic impregnated papers and then pressing them at high temperature and high pressure. When phenolic resin impregnated paper is used, a large amount of solvent needs to be added to improve the wettability of paper, resulting in rising costs and air pollution, which is not conducive to environmental protection development; and the price of phenolic resin is relatively expensive. Due to the use of multiple sheets of facial paper, the phenolic pad also needs to pay high processing costs, all of which make the use cost of phenolic pads always high. Currently, there are also pads made of cheaper and more environmentally friendly urea-formaldehyde resin impregnated facial paper. The impregnated facial paper is superimposed on the upper and lower parts of the wood fiber board, and pressed into shape under high temperature and high pressure to make an environmentally friendly pad for drilling small holes. However, it is easy to warp significantly, especially at high humidity (above 60%), and the warping exceeds the standard seriously.

[0003] Therefore, there is an urgent need for a preparation process that is low-cost, environmentally friendly and can make the prepared pad have low warpage and high hardness to meet market demand. Summary of the invention

[0004] In view of the defects in the prior art, the present invention proposes a urea-formaldehyde resin pad and a preparation process and application thereof.

[0005] The present invention provides a preparation process of a urea-formaldehyde resin pad, comprising the following steps:

[0006] Urea-formaldehyde resin is used to impregnate facial paper, and the impregnated facial paper is made into a prepreg after baking, and then the prepreg is respectively superimposed on the upper and lower sides of the wood fiber board, and finally pressed by a press to obtain the pad;

[0007] The urea-formaldehyde resin is obtained by reacting a compound of paraformaldehyde and a formaldehyde solution with a solubility of 35-40% with urea;

[0008] Urea-formaldehyde resin is synthesized from a complex of urea and formaldehyde, and uses water as a diluent, which is more environmentally friendly. Its price is 50% of that of phenolic resin, which can significantly reduce the cost of using the pad. The high-concentration formaldehyde after compounding has better stability and no precipitation problem. In addition, using wood fiber board as a supporting layer to replace multiple sheets of impregnated paper of the phenolic resin pad significantly reduces the wear of the drill bit, increases the service life of the drill bit, further reduces the overall cost of the pad, and makes the pad more environmentally friendly.

[0009] The inventors found that the urea-formaldehyde resin made by reacting a compound of polyformaldehyde and formaldehyde aqueous solution with urea has excellent waterproof performance after the glue is cured, which improves the problem of PP easily absorbing moisture and sticking after impregnation, improves production efficiency, and can better prevent the pad from warping in a high humidity environment;

[0010] The urea-formaldehyde resin pad prepared by the present invention has a simpler structure than the phenolic resin pad.

[0011] Furthermore, the surface paper has a grammage of 80-200 g / m 2 (weight of unimpregnated pure paper), such as 80, 100, 120, 140, 160, 180, 200g / m 2 By using high-weight surface paper for impregnation, the semi-cured sheet obtained has better strength after medium-temperature and high-pressure pressing, further solving the problem of easy warping of wood fiberboard after high-temperature pressing.

[0012] Furthermore, the thickness of the wood fiber board is 1.0-1.5 mm, such as 1.0, 1.1, 1.2, 1.3, 1.4, 1.5 mm.

[0013] Furthermore, the solid content of the urea-formaldehyde resin is 50-70%; the solid content of the urea-formaldehyde resin glue prepared by the present invention can be increased from the original 45% to 50%-70%, which can effectively improve the production efficiency of glue making, and the storage period of the glue can also be maintained at 4 days. The increase in the solid content of the glue means that the heat energy and water consumption required for glue making are reduced. When used for impregnation production, the urea-formaldehyde resin of the present invention has a lower heat required for baking due to the increase in solid content. Compared with the urea-formaldehyde resin impregnated facial paper prepared by simply using formaldehyde solution (baking speed is 16-18m / min), the baking speed will be increased by more than 50% under the same conditions (the baking speed of the impregnated facial paper of the present invention is 25-30m / min), and the PP after impregnation (facial paper after impregnation) is not easy to absorb moisture and stick, which is more conducive to production and use.

[0014] Furthermore, the temperature of the pressing operation is 90-120°C, such as 90, 95, 100, 105, 110, 115, 120°C, the pressure is 15-30MPa, such as 15, 18, 20, 22, 25, 28, 30MPa, and the pressing time is 30-120min, such as 30, 50, 60, 80, 100, 120min; the pressing temperature of the present invention is lower than that of the phenolic resin pad (the pressing temperature is above 140°C), so it has lower energy consumption in the production process, and because the pad of the present invention can be pressed at medium temperature, the warping can be further reduced.

[0015] Furthermore, the press forming also includes cooling the pressed pad in a cold press for 20-40 minutes before unloading the pad.

[0016] Furthermore, the mass ratio of the polyformaldehyde in the urea-formaldehyde resin to the formaldehyde solution with a solubility of 35-40% is 1:(0.33-3); if too much polyformaldehyde is added, polyformaldehyde precipitates will be produced during the glue making process, and the precipitation will cause the glue solution to precipitate, the glue solution synthesis will be unstable, and the precipitates will be brought into the paper after the paper is dipped in the glue, the drilling of the pad will easily result in skewed holes, and the CPK will be too low.

[0017] Furthermore, the molar ratio of the complex to urea is (1.5-2.5):1.

[0018] Furthermore, the preparation method of the urea-formaldehyde resin comprises the following steps:

[0019] S1. A high-concentration formaldehyde complex (solubility of 50-80%) is prepared by using paraformaldehyde and a formaldehyde solution with a solubility of 35-40%. The inventors found that if the formaldehyde complex exceeds this compound solubility, the paraformaldehyde will not be dissolved, resulting in the appearance of precipitates and causing the glue to be unstable. If it is lower than this compound solubility, the desired effect of the present invention cannot be achieved;

[0020] S2. The complex is mixed with urea in a molar ratio to carry out an addition (hydroxymethylation) reaction to generate monohydroxy, dihydroxy and trihydroxymethyl ureas.

[0021] The inventors found that by formulating formaldehyde complexes to increase the formaldehyde concentration in a large proportion, it is more conducive to the formation of dimethylol urea and trimethylol urea. The increase in the formation ratio of polymethylol urea is beneficial to improving the connection stability of the two-dimensional and three-dimensional structures of the resin, and the water absorption rate after curing is reduced by more than 50%.

[0022] The invention also provides a urea-formaldehyde resin pad prepared by the preparation process.

[0023] Furthermore, the backing plate has a Shore hardness of ≥80, a pencil hardness of ≥5H, and a warpage of <0.5%.

[0024] The present invention also provides the use of the urea-formaldehyde resin pad as a PCB drilling processing pad, especially as an environmentally friendly pad for drilling micro-holes in a PCB.

[0025] In summary, compared with the prior art, the present invention achieves the following technical effects:

[0026] (1) The urea-formaldehyde resin pad provided by the present invention has high hardness and low warpage, and can better protect the PCB board when used as a drilling pad;

[0027] (2) The urea-formaldehyde resin pad provided by the present invention has high drilling hole position accuracy when used in drilling processing, and can reduce the wear of the drill bit and increase the life of the drill bit;

[0028] (3) The drilling performance of the urea-formaldehyde resin pad provided by the present invention is comparable to that of the phenolic resin pad, and the cost is significantly reduced compared to the phenolic resin pad, thus having a high cost-performance ratio;

[0029] (4) The urea-formaldehyde resin pad preparation process provided by the present invention can significantly reduce the manufacturing cost of the drilling pad, and the preparation process is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 It is a schematic structural diagram of the urea-formaldehyde resin pad of the present invention;

[0032] Figure 2 Schematic diagram of the structure of the phenolic resin pad. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] Example

[0035] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.

[0036] 1. The sources of raw materials for the embodiments and comparative examples are as follows:

[0037] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present invention are commercially available.

[0038] Urea-formaldehyde resin #1: paraformaldehyde and 37% formaldehyde solution are compounded in a 1:1 ratio to form a high-concentration formaldehyde complex (solubility is 66.5%), and then mixed with urea in a molar ratio of 1:2 to obtain the compound;

[0039] Urea-formaldehyde resin #2: The difference from urea-formaldehyde resin #1 is that the compounding ratio is 3:1, and the formaldehyde complex (solubility is 80%);

[0040] Urea-formaldehyde resin #3: The difference from urea-formaldehyde resin #1 is that the compounding ratio is 1:3, and the formaldehyde complex (solubility is 50%);

[0041] Urea-formaldehyde resin #4: The difference from urea-formaldehyde resin #1 is that the compounding ratio is 4:1, and the formaldehyde complex (solubility is 85%);

[0042] Urea-formaldehyde resin #5: The difference from urea-formaldehyde resin #1 is that only a formaldehyde solution with a concentration of 37% is used.

[0043] The phenolic resin pad used in Comparative Example 3 is commercially available.

[0044] 2. Various performance test methods

[0045] (1) Platen warpage / pad high humidity condition warpage test (warpage (bow and twist) test): Tested in accordance with CPCA4403-2010.

[0046] (2) PP storage period (stickiness) test: Stickiness is when PP and PP are bonded together and cannot be separated or break after separation, resulting in poor appearance. At this time, the time from PP dipping to the appearance of stickiness is recorded, which is the PP storage period.

[0047] (3) Pad CPK index test: Use AOI precision scanner to test.

[0048] (4) Pad hardness test: Tested in accordance with GB / T 2411-2008.

[0049] Example 1

[0050] The urea-formaldehyde resin pad preparation process of Example 1 comprises the following steps:

[0051] Urea-formaldehyde resin #1 impregnated facial tissue (facial tissue weight 100g / m 2 ), the impregnated face paper is made into a semi-cured sheet after baking, and then the semi-cured sheets are respectively superimposed on the upper and lower sides of the wood fiber board (thickness of 1.0 mm), and finally pressed into shape by a press (pressing temperature of 100°C, pressure of 20 MPa, time of 60 min) to obtain the pad.

[0052] Example 2

[0053] The difference from Example 1 is that urea-formaldehyde resin #2 is used to impregnate the facial tissue.

[0054] Example 3

[0055] The difference from Example 1 is that urea-formaldehyde resin #3 is used to impregnate the facial tissue.

[0056] Example 4

[0057] The urea-formaldehyde resin pad preparation process of Example 4 comprises the following steps:

[0058] Urea-formaldehyde resin #1 impregnated facial tissue (facial tissue weight 180g / m 2 ), the impregnated face paper is made into a semi-cured sheet after baking, and then the semi-cured sheets are respectively superimposed on the upper and lower sides of the wood fiber board (thickness of 1.5 mm), and finally pressed by a press (pressing temperature of 120°C, pressure of 28 MPa, time of 110 min) to obtain the pad.

[0059] Example 5

[0060] The urea-formaldehyde resin pad preparation process of Example 5 comprises the following steps:

[0061] Urea-formaldehyde resin #1 impregnated facial tissue (facial tissue weight 140g / m 2 ), the impregnated face paper is made into a semi-cured sheet after baking, and then the semi-cured sheets are respectively superimposed on the upper and lower sides of the wood fiber board (thickness of 1.2 mm), and finally pressed by a press (pressing temperature of 95°C, pressure of 16 MPa, time of 40 min) to obtain the pad.

[0062] Comparative Example 1

[0063] The difference from Example 1 is that urea-formaldehyde resin #4 is used to impregnate the facial tissue.

[0064] Comparative Example 2

[0065] The difference from Example 1 is that urea-formaldehyde resin #5 is used to impregnate the facial tissue.

[0066] Comparative Example 3

[0067] Commercially available phenolic resin backing board.

[0068] Table 1 Effects of Examples and Comparative Examples

[0069]

[0070] The urea-formaldehyde resin in the urea-formaldehyde resin pads of Examples 1-5 is obtained by reacting a complex of polyformaldehyde and a formaldehyde solution with a solubility of 35-40% with urea, and the surface paper is impregnated with a specific resin, baked to form a semi-cured sheet, which is then stacked on a wood fiber board and pressed to form a pad. The prepared pad has high hardness, low warping, excellent punching performance, and a simple preparation process, which is environmentally friendly and greatly reduces the production cost of the drilling pad. Compared with commercially available phenolic resin pads, the present application can achieve comparable performance and can be used on a large scale.

[0071] Comparative Examples 1-3 are compared with Example 1. In Comparative Example 1, the amount of polyformaldehyde in the urea-formaldehyde resin used in the pad is too much, which makes the pad flatness poor and the CPK value significantly reduced; in Comparative Example 2, only 37% formaldehyde solution and urea are used to synthesize urea-formaldehyde resin, and the pad obtained has a high warpage rate and cannot be stably used in a high humidity environment; the phenolic resin pad used in Comparative Example 3 has a high production cost and is difficult to adapt to large-scale production in the market, and a large amount of organic solvents are used in the process of making phenolic resin, which will also cause environmental pollution. The above comparative examples cannot make the drilling pad obtained have excellent drilling performance while reducing the production cost and making the preparation process environmentally friendly.

[0072] Based on the test data of the warpage, CPK and hardness of the prepared pads in Table 1, the urea-formaldehyde resin pads prepared by Examples 1-5 have obvious advantages over the comparative examples and can effectively meet the high standards of customers and the market.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A process for preparing a urea-formaldehyde resin pad, characterized in that: The steps include: Urea-formaldehyde resin is used to impregnate facial paper, and the impregnated facial paper is made into a prepreg after baking, and then the prepreg is respectively superimposed on the upper and lower sides of the wood fiber board, and finally pressed by a press to obtain the pad; The urea-formaldehyde resin is obtained by reacting a compound of paraformaldehyde and a formaldehyde solution with a solubility of 35-40% with urea.

2. The preparation process according to claim 1, characterized in that: The surface paper weight is 80-200g / m 2 .

3. The preparation process according to claim 1, characterized in that: The thickness of the wood fiber board is 1.0-1.5 mm.

4. The preparation process according to claim 1, characterized in that: The solid content of the urea-formaldehyde resin is 50-70%.

5. The preparation process according to claim 1, characterized in that: The pressing operation is performed at a temperature of 90-120° C., a pressure of 15-30 MPa, and a pressing time of 30-120 min.

6. The preparation process according to claim 1, characterized in that: The mass ratio of the paraformaldehyde in the urea-formaldehyde resin to the formaldehyde solution with a solubility of 35-40% is 1:(0.33-3).

7. The preparation process according to claim 1, characterized in that: The molar ratio of the complex to urea is (1.5-2.5):

1.

8. Urea-formaldehyde resin pad prepared by the preparation process according to any one of claims 1 to 7.

9. The urea-formaldehyde resin pad according to claim 8, characterized in that: The backing plate has a Shore hardness of ≥80, a pencil hardness of ≥5H, and a warpage of <0.5%.

10. Use of the urea-formaldehyde resin pad according to claim 9 as a pad for PCB drilling processing.

Citation Information

Patent Citations

  • Laminating base plate for boring and preparing method thereof

    CN103950057A

  • Environment-friendly co-condensed resin wood adhesive with high solid content, and preparation method and application thereof

    CN107603541A

  • Preparation method of lignin modified environment-friendly urea-formaldehyde resin adhesive

    CN112625627A

  • Manufacturing method for woody laminate

    JP2004001266A

  • Eco-friendly exterior panel with excellent flame retardant

    KR102137408B1